Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-020-66066-x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance-related depressive symptom and brain volume reduction in shift-working nurses

Abstract: Disturbed sleep is the most common effect of shift work. A large corpus of research indicates an association between sleep disturbance and depressive symptom in shift workers. In this study, we proposed the mediating role of grey matter (GM) structure in the relationship between sleep disturbance and depressive symptom. We collected structural MRI (sMRI) data as well as assessing the level of sleep disturbance and depressive symptom with the Pittsburgh Sleep disturbance Index and Zung Self-Rating Depression Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 43 publications
0
24
0
3
Order By: Relevance
“…When this is done, the circadian system is unable to fully adjust to the shift work, and therefore humans are only able to stay awake at night because the masking system is overriding the endogenous circadian rhythm that is misaligned with behavior ( Vokac et al, 1981 ). Nurses that engage in many years of shift work have been shown to be at a higher risk of developing breast cancer ( Szkiela et al, 2020 ), depression ( Booker et al, 2020 ; Park et al, 2020 ), and anxiety ( Booker et al, 2020 ). Animal models of shift work with nocturnal mice have also revealed the deleterious effects of misaligning circadian rhythms and behavior which occurs due to effects of masking, but that these effects are most severe when the organism is expected to flip-flop their behavior on days of work vs. days of rest, also known as “circadian desynchrony” ( Barclay et al, 2012 ).…”
Section: Masking Interacts With the Circadian And Homeostatic Systems...mentioning
confidence: 99%
“…When this is done, the circadian system is unable to fully adjust to the shift work, and therefore humans are only able to stay awake at night because the masking system is overriding the endogenous circadian rhythm that is misaligned with behavior ( Vokac et al, 1981 ). Nurses that engage in many years of shift work have been shown to be at a higher risk of developing breast cancer ( Szkiela et al, 2020 ), depression ( Booker et al, 2020 ; Park et al, 2020 ), and anxiety ( Booker et al, 2020 ). Animal models of shift work with nocturnal mice have also revealed the deleterious effects of misaligning circadian rhythms and behavior which occurs due to effects of masking, but that these effects are most severe when the organism is expected to flip-flop their behavior on days of work vs. days of rest, also known as “circadian desynchrony” ( Barclay et al, 2012 ).…”
Section: Masking Interacts With the Circadian And Homeostatic Systems...mentioning
confidence: 99%
“…Compared to day-workers reduced STG volume has been reported among shift workers who also reported more sleep disturbances and depressive symptoms. [43] Further, thinner STG has also been reported in patients with obstructive sleep apnea (OSA). [44] In our study, five NT1 patients had AHI ≥ 5, however these patients were excluded from the sensitivity analysis which largely supported the results from the main analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Written informed consent from all participants was obtained in accordance with the Declaration of Helsinki and its later amendments. The study was approved by the Institutional Review Board at the Seoul St. Mary's Hospital, Seoul, Korea [24].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that alterations in circadian rhythm are a primary risk factor for symptom development in individuals with BSDs, along with other deleterious effects on metabolic and cardiovascular health [21][22][23]. Park et al [24] discovered structural changes in the brains of shift-working nurses compared to those who worked days. The authors found decreased volume in the post-central gyrus, right paracentral lobule, and left superior temporal gyrus.…”
Section: Stress Shift Work and Sleepmentioning
confidence: 99%